2018
DOI: 10.3390/genes9090434
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analyses of a Putative, Membrane-Bound, Peroxisomal Protein Import Mechanism from the Apicomplexan Protozoan Toxoplasma gondii

Abstract: Peroxisomes are central to eukaryotic metabolism, including the oxidation of fatty acids—which subsequently provide an important source of metabolic energy—and in the biosynthesis of cholesterol and plasmalogens. However, the presence and nature of peroxisomes in the parasitic apicomplexan protozoa remains controversial. A survey of the available genomes revealed that genes encoding peroxisome biogenesis factors, so-called peroxins (Pex), are only present in a subset of these parasites, the coccidia. The basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…However, the existence of peroxisome per se in T. gondii has long been questioned and remains a debated topic as (i) the typical organelle’s presence remains elusive or not fully defined, and (ii) there is no clear experimental evidence for biochemical activities attributed to such predicted organelle compartment(s). Interestingly the PTS found in Tg ACS1 is similar to the one identified in other Toxoplasma proteins and is able to rescue peroxisomal import assay in yeast mutant ( 38 ). Using Alphafold and a 3D crystal structure of a bubble gum domain-containing ACS found in Mycobacterium tuberculosis ( 47 ), which shares 51% of sequence identity with Tg ACS1, we thus generated a 3D model prediction ( Fig.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…However, the existence of peroxisome per se in T. gondii has long been questioned and remains a debated topic as (i) the typical organelle’s presence remains elusive or not fully defined, and (ii) there is no clear experimental evidence for biochemical activities attributed to such predicted organelle compartment(s). Interestingly the PTS found in Tg ACS1 is similar to the one identified in other Toxoplasma proteins and is able to rescue peroxisomal import assay in yeast mutant ( 38 ). Using Alphafold and a 3D crystal structure of a bubble gum domain-containing ACS found in Mycobacterium tuberculosis ( 47 ), which shares 51% of sequence identity with Tg ACS1, we thus generated a 3D model prediction ( Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Very interestingly, two studies independently identified strong homologs of PEX in T. gondii , notably Tg PEX5, all bearing putative PTS and most likely allowing peroxisome biogenesis and protein import. Indeed, PEX5 can recognize and bind to the proteins bearing a PTS1, allowing the transport of any soluble proteins destined to peroxisomal lumen ( 37 , 38 ). It was further demonstrated that the PTS1-binding domain of Tg PEX5, which is usually enabling peroxisomal protein import in eukaryotes, was interacting with the PTS1 of Tg SCP2 in vitro ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, chromalveolates and particularly stramenopiles are amazingly heterogeneous with respect to both the presence of peroxisomes and the PTS2 import pathway. Non-coccidian apicomplexa (e.g., Plasmodium) lack peroxisomes entirely, while coccidian apicomplexa (e.g., Toxoplasma) possess solely the PTS1 import pathway (Schluter et al, 2006;Mbekeani et al, 2018), similar to nowadays red algae (Matsuzaki et al, 2004;Shinozaki et al, 2009). As shown by this study, some stramenopiles have maintained both pathways (Eustigmatophyceae, brown algae), while diatoms lost the PTS2 pathway entirely and transferred classical PTS2 cargo proteins (e.g., thiolase) to the PTS1 import pathway (Figure 6; Gonzalez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%